T-bet suppresses proliferation of malignant B cells in chronic lymphocytic leukemia - Rößner, Philipp M.; Seufert, Isabelle; Chapaprieta, Vicente; Jayabalan, Ruparoshni; Briesch, Hannah; Massoni-Badosa, Ramon; Boskovic, Pavle; Benckendorff, Julian; Roider, Tobias; Arseni, Lavinia; Coelho, Mariana; Chakraborty, Supriya; et al. (Blood, 2024)
The T-box transcription factor T-bet is known as a master regulator of the T-cell response but its role in malignant B cells has not been sufficiently explored. Here, we conducted single-cell resolved multi-omics analyses of malignant B cells from patients with chronic lymphocytic leukemia (CLL) and studied a CLL mouse model with a genetic knockout of Tbx21. We found that T-bet acts as a tumor suppressor in malignant B cells by decreasing their proliferation rate. NF-κB activity, induced by inflammatory signals provided by the microenvironment, triggered T-bet expression, which affected promoter-proximal and distal chromatin coaccessibility and controlled a specific gene signature by mainly suppressing transcription. Gene set enrichment analysis identified a positive regulation of interferon signaling and negative control of proliferation by T-bet. In line, we showed that T-bet represses cell cycling and is associated with longer overall survival of patients with CLL. Our study uncovered a novel tumor suppressive role of T-bet in malignant B cells via its regulation of inflammatory processes and cell cycling, which has implications for the stratification and therapy of patients with CLL. Linking T-bet activity to inflammation explains the good prognostic role of genetic alterations in the inflammatory signaling pathways in CLL.
Gesehen am 10.07.2025